Rural extension approaches for the development of blackberry producers in the department of Caldas - Henao-Castaño, Angélica María; Tobasura-Acuña, Isaías (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Rural Extension has been one of the strategies used to help farmers to improve their production systems and thus contribute to their well-being. To achieve these purposes, the institutions and entities providing this service use different approaches. This work compiles the differences and similarities in the rural extension approaches that the Universidad de Caldas and the Horticultural Association of Colombia (Asohofrucol) have used during the last six 6 years with blackberry producers in the municipalities of Aranzazu and Manzanares (Caldas). To gather information, we interviewed local and regional authorities, professors and extension workers; we reviewed literature, documentaries and institutional sources; and put together workshops with producers, developing a participatory diagnosis. Furthermore, we organized Farming Schools, outdoor days and training for facilitators. This work allowed us to conclude that although the two institutions share purposes and use similar extension methods, the approaches are different.